Effects of COVID-19 on Autism Spectrum Disorder in Qatar - Alshaban, Fouad A.; Ghazal, Iman; Al-Harahsheh, Sanaa T.; Lotfy, Mustafa; Al-Shammari, Hawraa; Al-Faraj, Fatema; Thompson, I. Richard; Ratto, Allison B.; Nasir, Assal; Tolefat, Mohamed (Frontiers in Psychiatry, 2024)
Introduction: The unprecedented impact of the coronavirus pandemic (COVID-19) has had profound implications on the ASD community, including disrupting daily life, increasing stress and emotional dysregulation in autistic children, and worsening individual and family well-being. Methods: This study used quantitative and qualitative survey data from parents in Qatar (n=271), to understand the impact of the COVID-19 pandemic on autistic children and their families in Qatar. The questionnaire was a combination of open-ended (qualitative) and closed-ended (quantitative) questions to explore patterns in the experiences of the different families, as well as to contrive themes. The survey was created in a way to evaluate the psychological, academic/intervention, economic, and other impacts of the pandemic related measures on a sample of multicultural families residing in the State of Qatar during the peak period of confinement and physical distancing in 2020. Data acquisition involved the utilization of Google Forms. Subsequent quantitative analysis employed the SPSS software and chi-square analysis for numerical examination, enabling the characterization of the studied population and exploration of associations between parental stress levels and variables such as employment status, therapy accessibility, presence of hired assistance, and alterations in their child's skills. Concurrently, qualitative data from written responses underwent thorough categorization, encompassing themes such as emotional isolation, mental or financial challenges, and difficulties in obtaining support. Results: Parents expressed distress and disturbance in their daily lives, including profound disruptions to their children's access to treatment, education, and activities. Most parents reported deteriorations in their children's sleep (69.4%), behavioral regulation (52.8%), and acquired skills across multiple domains (54.2%). Parents also reported decreased access to family and social support networks, as well as decreased quality of clinical and community support. Qualitative analysis of parental responses revealed that child developmental regression was an important source of parental stress. Discussion and Conclusion: The greater impact of the pandemic on autistic children and their families emphasizes the need for accessible and affordable health, education, and family services to manage their special needs.